Flexible Firm : the Design of Culture at Bang & Olufsen. - Krause-Jensen, Jakob (Berghahn Books, Inc., 2010)
Bang & Olufsen, the famous Danish producer of high-end home electronics, is well known as an early exponent of value-based management: the idea that there should be consistency in what the organisation does, a certain continuity between what the company develops and sells, and the beliefs and practices of the employees. This study investigates how company values are communicated and the collective identity is articulated through the use of such concepts as 'culture', 'fundamental values', and 'corporate religion', as well as how employees negotiate these ideas in their daily working lives. As.